Serum Amyloid A in the Placenta and Its Role in Trophoblast Invasion - Sandri, Silvana (Public Library of Science, 2014)
The serum amyloid A (SAA) protein is known to function in the acute phase response and immunoregulation. Recently, SAA has been shown to be involved in cell proliferation, differentiation and migratory behavior in different cell types. Here, we evaluated whether exogenous SAA could influence trophoblast invasion and differentiation using both the trophoblast-like BeWo cell line and fully differentiated human extravillous trophoblast cells (EVT) isolated from term placentae. SAA stimulated BeWo cell invasion, as measured in Matrigel invasion assays, and induced metalloprotease mRNA expression and activity. Given that BeWo cells express Toll-like receptor 4 (TLR4), a known receptor for SAA, we examined the role of TLR4 in SAA-induced invasion using a TLR4 neutralizing antibody. We also tested whether SAA could affect markers of trophoblast syncytialization in BeWo cells. We observed that SAA decreased βhCG secretion and did not influence trophoblast syncytialization. Using EVT cells isolated from human term basal plates, we confirmed that SAA at 1 and 10 µg/mL doubled EVT invasion in a TLR4-dependent manner, but at 20 µg/mL inhibited EVT cells invasiveness. In addition, we observed that SAA was expressed in both BeWo cells and human term placentae, specifically in the syncytiotrophoblast, decidual cells and EVT. In conclusion, SAA was identified as a molecule that functions in the placental microenvironment to regulate metalloprotease activity and trophoblast invasion, which are key processes in placentation and placental homeostasis.